Effectiveness of Neuromuscular Electrical Stimulation and Dynamic Mobilization Exercises on Equine Multifidus Muscle Cross-Sectional Area - Gómez Lucas, Raquel; Rodríguez Hurtado, Isabel; Troteaga Álvarez, Carla; Ortiz, Gustavo (My University, 2022)
Equine back pain can potentially initiate an unstable intervertebral situation that results in atrophy and dysfunction of the epaxial muscles even after back pain has resolved. Several physiotherapy approaches are advocated to promote the strengthening of the multifidus muscle. This study aimed to asses and compare the effect of dynamic mobilization exercises (DME) and neuromuscular electrical stimulation (NMES) in 8 adult horses (4 individuals by group) to increase the cross-sectional area (CSA) of this muscle after a 7-weeks period treatment. The epaxial muscles of NMES group were electrical stimulated during 10 minutes per session, 4 days a week for 7 weeks, yielding a total of 28 sessions per individual. Horses included in DME group were trained to move the chin to a specific position (three different cervical flexions, one cervical extension and three different lateral bending exercises) to the left and right sides, repeated 5 times per session, completing 28 sessions. Ultrasonographic images of the left and right multifidus muscle were acquired at 3 different spinal locations (T12, T16 and L2) at the initial and the end of the experiment. Significant increases (P < .050) in its CSA were obtained at all levels considered (except at T16), consistent with a 18.65% and 13.41% increase after NMES and DME, respectively. These results suggest that a 7-week period of DME or NMES treatments are useful to increase the CSA of the multifidus muscle in horses, and hence, these two therapies could be combined during a back-rehabilitation program to improve the spine stabilization in horses